2000
DOI: 10.1165/ajrcmb.23.2.4035
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Particulate Matter Causes Expression of Nuclear Factor (NF)- κ B–Related Genes and Oxidant-Dependent NF- κ B ActivationIn Vitro

Abstract: High levels of ambient air pollution are associated with exacerbation of asthma and respiratory morbidity, yet little is known concerning the mechanisms of inflammation and toxicity by components of inhaled particulate matter (PM). Brief inhalation of PM(2.5) (particles of an aerodynamic diameter of < 2.5 microns) (300 microg/m(3) air for 6 h followed by a period of 24 h in clean air) by either C3H/HeJ or C57/BL6 mice caused significant (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
137
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(150 citation statements)
references
References 25 publications
9
137
1
3
Order By: Relevance
“…In addition, target cells, such as airway epithelial cells and macrophages, generate ROS in response to particle uptake by biologically catalysed oxidation reactions that occur in the cell membrane and mitochondria [4,[40][41][42]. In vitro studies have shown that inhaled PM causes expression of nuclear factor (NF)-kB-related genes and oxidant-dependent NF-kB activation [43,44]. The dose of bio-available transition metal, rather than particulate mass, may be the primary determinant of acute inflammatory response [35,37,44].…”
Section: Biological and Epidemiological Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, target cells, such as airway epithelial cells and macrophages, generate ROS in response to particle uptake by biologically catalysed oxidation reactions that occur in the cell membrane and mitochondria [4,[40][41][42]. In vitro studies have shown that inhaled PM causes expression of nuclear factor (NF)-kB-related genes and oxidant-dependent NF-kB activation [43,44]. The dose of bio-available transition metal, rather than particulate mass, may be the primary determinant of acute inflammatory response [35,37,44].…”
Section: Biological and Epidemiological Evidencementioning
confidence: 99%
“…In vitro studies have shown that inhaled PM causes expression of nuclear factor (NF)-kB-related genes and oxidant-dependent NF-kB activation [43,44]. The dose of bio-available transition metal, rather than particulate mass, may be the primary determinant of acute inflammatory response [35,37,44]. However, other studies suggest that the hydrosoluble fraction is responsible for the oxidative damage to DNA [45].…”
Section: Biological and Epidemiological Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression was assessed qualitatively and quantitatively using the MultiProbe RPA system (Riboquant; BD Pharmingen) (21). The murine cytokine template set mCK-5c was used on RNA from 9 day animals (the time of peak inflammation) using radiolabeled antisense RNA probes for Ltn, RANTES, mip-␣, mip-1␤, mip-2, IP-10, mcp-1, tca-3, eotaxin, L32, and gapdh.…”
Section: Rna Isolation and Rnase Protection Assays (Rpa)mentioning
confidence: 99%
“…Oxidative stress is induced in these cells 16 . The inflammatory response was studied in mice, in which inhalation of 300 µm 3 of PM 2.5 caused increase in TNF-β, interferon-β, IL-6 and transforming growth factor-β 17 . The carbon particles, the important constituents of PM 10, cause the release of immature neutrophils from the bone marrow, underlining the chief role of PM in pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%